Apartamentos mínimos contemporâneos: análises e reflexões para obtenção de sua qualidade - Mendonça, Rafaela Nunes (2015)
The phenomenon of minimization of the residences, especially of the apartments, it is noticeable and not restricted only to low-income housing and can be seen even in buildings with higher values. A common problem in most of these households, is unsatisfactory and inappropriate manner with which respond to contemporary modes of living. The objectives of this research were to analyze the inadequacies created by the minimization of contemporary apartments, their effects on modes of living, make recommendations that guided the functional quality improvement of these spaces, through a more intense relationship between design and architecture. Projects launched in the city of Uberlândia-MG between 2010 and 2015, aimed at the middle class from pre-established criteria were adopted as objects of study. The analysis also focused on furniture and equipment essential to the domestic dynamics of these apartments, available in retail and department stores present in the city, however, of national scope. Minimizing, exacerbated by physical constraints, functional construction and the building, placing the physical dimensions and use of the equipment and furniture that makes up the housing arrangement. The restriction on the modes of living occur insofar as such and make overlays of adverse activities, as well as, disregard changes in profiles of residents and their needs for adaptation and appropriation in the course of time. Solutions have been shown to meet the concept of use, flexibility, fitness, ownership, privacy and ergonomics. The Organization of space, part of the knowledge about the furniture and equipment needed for the domestic dynamics and these, in turn, must be designed for modularity and adaptability. The analyses developed front each concept, identified and highlighted the main problems of incompatibility and inadequacy, resulting in recommendations to address the use, flexibility, fitness, ownership, privacy and ergonomics. We conclude that actions aiming to design strategies of modularity and adaptability to the furniture and equipment, are collaborators for the housing become consistent to its destination by establishing healthy relationship between home and resident.